2022
DOI: 10.3325/cmj.2022.63.265
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal signaling cells niche in stromal vascular fraction from lipoaspirate and microfragmented counterpart

Abstract: Aim To expand our previous findings by increasing the number of patients in a study characterizing medicinal signaling cells (MSC) of stromal vascular fraction from lipoaspirate (SVF-LA) and from microfragmented lipoaspirate (SVF-MLA) applied for the treatment of osteoarthritis (OA).Methods Twenty OA patients, including 8 new patients, acquiring autologous microfragmented adipose tissue were enrolled. In-parallel immunophenotyping of SVF-LA and SVF-MLA was performed. The samples were incubated in a DuraClone S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Autologous micro-fragmented adipose tissue contains mesenchymal stem cells (MSCs) that additionally have regenerative and immunomodulatory effects. Moreover, recent studies revealed gender-dependent differences in the stromal vascular fraction from lipoaspirate and micro-fragmented adipose tissue, which implies different therapeutic responses are needed in men and women [13]. These new findings indicate a potential beneficial effect of cell therapy in hair growth stimulation in addition to the currently tested PRP treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Autologous micro-fragmented adipose tissue contains mesenchymal stem cells (MSCs) that additionally have regenerative and immunomodulatory effects. Moreover, recent studies revealed gender-dependent differences in the stromal vascular fraction from lipoaspirate and micro-fragmented adipose tissue, which implies different therapeutic responses are needed in men and women [13]. These new findings indicate a potential beneficial effect of cell therapy in hair growth stimulation in addition to the currently tested PRP treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Mesenchymal stem cells (MSCs) are multipotent adult stem cells that have the ability to differentiate into a variety of cell types (adipocytes, osteoblasts, myocytes, chondrocytes, etc.) dictated by the given milieu [ 35 , 40 , 41 , 42 , 47 , 48 , 49 ]. Regarding origin, MSCs can be extracted from the bone marrow (BM-MSCs), umbilical cord MSCs (UC-MSCs), amniotic fluid SCs (AF-SC), placental MSCs (P-MSC), menstrual blood SCs (Men-SC), breast milk, cervix, dental tissue, synovial tissue, and fluid, or can be adipose-derived MSCs (AD-MSCs) and amnion-derived MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Via polychromatic flow cytometric analysis, earlier, we determined the phenotypes of the CD45 subpopulation in autologous micro-fragmented samples containing the stromal vascular fraction (SVF). The most predominant cells include endothelial progenitors (EP) (CD31+ CD34+ CD73± CD90± CD105± CD146±), mature endothelial cells (CD31+ CD34− CD73± CD90± CD105− CD146±), pericytes (CD31− CD34− CD73± CD90+ CD105− CD146+), transitional pericytes (CD31− CD34+ CD73± CD90+ CD105− CD146+), and supra-adventitial-adipose stromal cells (CD31− CD34+ CD73high CD90+ CD105− CD146−) [ 48 , 49 ]. On the other hand, MSCs express very low levels of surface antigens and therefore do not trigger an immune response, allowing their usage as therapeutic agents in regenerative medicine [ 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pool of proliferating APCs is located in the stromovascular fraction of adipose tissue and is a depot and sex-and age-dependent [31,40,45,49,50]. Ex vivo and in vivo human studies have identified APC types among CD31− and CD34+ stromal vascular fractions [51][52][53][54][55][56][57]. Similarly, in a mice-specific sub-population characterized by cell surface immune markers was identified to possess proliferation and differentiation pro-adipogenic functional capabilities [51,53,54].…”
Section: Adipocyte Hyperplasiamentioning
confidence: 99%